Clinical Queries Addressed in Patients with Systemic Autoimmune Diseases. Can Cardiovascular Magnetic Resonance Give the Final Solution? - Mavrogeni, Sophie; Karabela, Georgia; Gialafos, Elias; Spiliotis, George; Pentazos, George; Mylona, Maria; Panopoulos, Stelios; Plastiras, Sotirios; Kolovou, Genovefa; Stavropoulos, Efthymios; Boutsikou, Maria; Kitas, George; et al. (Inflammation & Allergy-Drug Targets (Discontinued), 2014)
Objectives: To evaluate the potential of cardiovascular magnetic resonance (CMR) to answer queries, addressed in systemic autoimmune diseases (SAD). Methods: Thirty-six patients aged 52±6 years, (range 27-71) with SAD and suspected cardiac disease underwent CMR by a 1.5 T, after routine evaluation, including clinical, ECG and echocardiographic examination. Steady-state, free precession cines, STIR T2-W and late gadolinium enhanced (LGE) images were evaluated. Results: Abnormal findings were detected by: clinical evaluation in 14/36, ECG in 17/36, echocardiography in 11/36 and CMR in 30/36 SAD. Clinical, ECG and echocardiographic examination could not assess cardiac disease acuity and lesions’pathophysiology. In contrary, CMR identified cardiac lesions’ etiology, acuity, need for catheterization and heart disease persistence, even if SAD was quiescent. Conclusion: Clinical, ECG and echocardiographic abnormalities may suggest, but not always interpret cardiac involvement in SAD. CMR can help to identify both etiology and acuity of cardiac lesions and guide further diagnostic and/or therapeutic approach in these patients.
Keywords: ECG